Assessment of the technical condition of tyres used in agricultural and forestry machinery - Gorzelańczyk, Piotr; Rochowiak, Łukasz (Ocena stanu technicznego ogumienia wykorzystywanego w maszynach rolniczych i leśnych, 2019)
The article addresses the issues related to the testing of properties and assessment of the impact of factors forcing the replacement of tires in agricultural and forestry machines. This is a significant problem regarding the conditions of operation and use of agricultural and forestry machinery, which affects the withdrawal of tires from further use. The first part of the article presents the characteristics of tires for agricultural and forestry machines, presenting their structure, advantages and disadvantages, and the most common damage. In the second and at the same time the main part of the article, the tires of agricultural and forestry machines were examined, and the results and analysis of the conducted measurement tests were presented. The work ends with conclusions that appeared during the tests and proposed solutions for users of the tested tires
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2019, Nr 2 (33), s. 60-70